2003
DOI: 10.1200/jco.2003.05.157
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Care Indicators for Early-Stage Prostate Cancer

Abstract: This study establishes a foundation on which to build quality-of-care assessment tools to evaluate the treatment of early-stage prostate cancer. The next step is to field-test the indicators for feasibility, reliability, validity, and clinical utility in a population-based sample. This work will begin to inform medical decision-making for patients and their physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
1
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 50 publications
1
111
1
6
Order By: Relevance
“…15 Prior studies have observed that patients choosing surgery over other modalities, or robotic-assisted over open surgery, may later express regret over their decisions. 16,17 For localized prostate cancer, for which there is no optimal treatment and morbidities differ, promoting access to multiple providers holds the potential for enhancing the informed decision-making process, framing appropriate expectations, reducing treatment regret, and thereby improving post-treatment quality of life.…”
Section: Expectant Managementmentioning
confidence: 99%
“…15 Prior studies have observed that patients choosing surgery over other modalities, or robotic-assisted over open surgery, may later express regret over their decisions. 16,17 For localized prostate cancer, for which there is no optimal treatment and morbidities differ, promoting access to multiple providers holds the potential for enhancing the informed decision-making process, framing appropriate expectations, reducing treatment regret, and thereby improving post-treatment quality of life.…”
Section: Expectant Managementmentioning
confidence: 99%
“…They are relatively easy and inexpensive to assess, but tend to be only weakly associated with outcomes, and are often difficult for providers to influence. Structural measures often work best at establishing a minimal threshold for quality-for example, suggesting that radiation therapy for prostate cancer should be provided at centers with access to intensity modulated delivery systems [6]-thus distinguishing good from inferior but not good from superior. One structural aspect of health care delivery that is the subject of much ongoing debate in urologic oncology and across multiple other fields in medicine is the extent to which hospital and clinician case volume predict outcomes, which will be discussed in more detail below and elsewhere in this seminar [7].…”
Section: Assessing Qualitymentioning
confidence: 99%
“…One appealing framework applicable to the latter situation is the National Surgical Quality Improvement Program (NSQIP) developed by the Department of Veterans Affairs (VA) [17] and recently extended to non-VA hospitals [18]. Spencer et al, likewise, have developed a set of quality indicators specific to surgical and radiation-based treatment of localized prostate cancer, which incorporates a mix of structure, process, and outcomes measures [6].…”
Section: Assessing Qualitymentioning
confidence: 99%
“…This was done most comprehensively in 2000 by RAND. 2 More recently, the Physician Consortium for Performance Improvement (PCPI) and the National Quality Forum (NQF) endorsed several quality measures, incorporating some of the RAND measures and an up-to-date evidence base. 3,4 Three of these measures have also been included into the Centers for Medicare and Medicaid Services' Physician Quality Reporting System.…”
Section: Introductionmentioning
confidence: 99%